A method for minimization of cladding failure parameter accumulation probability in VVER fuel elements - Pelykh, S.N.; Maksimov, M.V.; Nikolsky, M.V. (Вопросы атомной науки и техники, 2014)
It has been proved, that under normal operating conditions the following methods of VVER fuel cladding
durability control can be considered as main ones: control of fuel element (FE) construction and fuel physical
properties, e.g. making fuel pellets of the most strained axial segment with center holes – M(1); control of the
regulating group disposition – M(2); control of the balance of VVER loading regimes – M(3); control of the coolant
temperature regime – M(4); control of the FA rearrangement algorithm – M(5). Based on М(i), i = [1,…,5], a
method for minimization of cladding failure parameter accumulation probability in VVER fuel elements by means
of control of FE properties at the reactor design and operation stages, lowering the probability of FE cladding failure
and increasing the uniformity of burnup, has been developed. Доказано, что при нормальных условиях эксплуатации следующие методы управления долговечностью
оболочек твэлов ВВЭР можно рассматривать как основные: управление конструкционными свойствами
твэла и физическими свойствами топлива, например изготовление топливных таблеток наиболее
напряженного аксиального сегмента с центральными отверстиями – M(1); управление расположением
регулирующей группы – M(2); управление балансом режимов нагружения ВВЭР – M(3); управление
температурным режимом теплоносителя – M(4); управление алгоритмом перестановок ТВС – M(5).
Основываясь на М(i), i = [1,…,5], разработан метод минимизации вероятности накопления поврежденности
оболочек твэлов ВВЭР путем управления свойствами твэлов на стадиях проектирования и эксплуатации
реактора, позволяющий снизить вероятность разгерметизации оболочек и повысить равномерность
выгорания топлива. Доведено, що за нормальних умов експлуатації наступнi методи управління довговічністю оболонок
твелів ВВЕР можна розглядати як основні: управління конструкційними властивостями твела і фізичними
властивостями палива, наприклад виготовлення паливних пігулок найбільш напруженого аксіального
сегмента з центральними отворами – M(1); управління розташуванням регулюючої групи – M(2); управління
балансом режимів навантаження ВВЕР – M(3); управління температурним режимом теплоносія – M(4);
управління алгоритмом перестановок ТВЗ – M(5). Грунтуючись на М(i), i = [1,…,5], розроблений метод
мінімізації імовірності накопичення пошкодженості оболонок твелів ВВЕР шляхом управління
властивостями твелів на стадіях проектування і експлуатації реактора, що дозволяє зменшити вірогідність
розгерметизації оболонок і підвищити рівномірність вигорання палива.